Brinell Hardness Testing of Shielding Wax Paraffin for Cancer Therapy Facilities with BNCT Method in Kartini Reactor Beamport - Alexander Eka Susanto (Indonesian Journal of Physics and Nuclear Applications, 2019)
Hardness testing is used to investigate the hardness of metallic material. Hardness tests are performed frequently because it is simple, inexpensive, and other mechanical properties can be estimated from hardness such as tensile strength. The basic concept of hardness testing is pressing a hard point or round ball against surface material. The Brinell hardness is used in this experiment. The Brinell hardness number is determined fpom the diameter of indentation. This study will investigate the hardness number of aluminium shielding of wax Paraffin, three sample specimens of aluminium plate with dimensions of 5x5 cm and thickness of 3 mm. The result from the test is 30.89 BHN